Dynamic Changes of Cauda Equina Motion Before and After Decompressive Laminectomy for Lumbar Spinal Stenosis With Redundant Nerve Roots: Cauda Equina Activation Sign - Kawasaki, Yosuke (Global Spine J, 2019)
STUDY DESIGN: Cross-sectional observational study (consecutive case series). OBJECTIVES: The aim of this study was to define a criterion for achieving successful decompression of lumbar spinal stenosis (LSS) using intraoperative ultrasonography (IOUS) and to investigate the pathogenesis of redundant nerve roots (RNRs) based on the ultrasonographic findings. METHODS: A total of 100 LSS patients (71 males, 29 females, mean age, 71 ± 8 years) with RNRs were enrolled as subjects in this study. IOUS was performed to evaluate pulsatile motion of the cauda equina (PMCE) just before and after decompressive laminectomy. To determine the decompression status of the cauda equina, the ultrasonographic findings were classified into 3 types on the basis of the presence or absence of PMCE: type 1, predecompression PMCE (−) to postdecompression PMCE (+); type 2, pre- and postdecompression PMCE (+); and type 3, pre- and postdecompression PMCE (−). The pathogenesis of RNRs was also investigated based on the ultrasonographic findings. RESULTS: Around the stenosis, PMCE was almost always absent before decompression and appeared after decompression (type 1 in 94 patients, type 2 in 6, type 3 in 0). IOUS showed that, before decompression, the cauda equina was held at the stenosis and could not pulsate beyond the stenotic site, and after decompression, PMCE recovered in the craniocaudal direction, leading to the resolution of RNRs. CONCLUSIONS: The emergence of PMCE can be a sign of successful decompression for LSS. Ultrasonographic findings support the notion that disturbance of PMCE around the stenosis is a basic component of the pathogenesis of RNRs.